VERTICAL FISCAL IMBALANCE AND THE FINANCIAL INDEPENDENCE OF LOCAL BUDGETS: THEORETICAL FOUNDATIONS AND INSTITUTIONAL MECHANISMS - Muxitdinov Sidikkhoja Akobirkhoja ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article examines the concept of vertical fiscal imbalance and its impact on the financial autonomy of local budgets from both theoretical and institutional perspectives. The study is grounded in fiscal federalism theory, intergovernmental fiscal relations, and the processes of centralization and decentralization. Vertical fiscal imbalance is interpreted as a mismatch between revenue and expenditure assignments across different levels of government, and its implications for transfer dependency and fiscal autonomy are analyzed. The paper also distinguishes between de jure and de facto fiscal decentralization. Based on the findings, institutional mechanisms aimed at strengthening the financial independence of local budgets are proposed.